The Legacy of Agrarian Reform in Latin America: Foundations of the Fair Trade Cooperative System. Issue 12 (December 2016) - Bruce, Analena
Abstract: Cooperatives are essential to the success of fair trade because small farmers must be organized into cooperatives in order to be certified. Fair trade aims to empower small farmers, yet many farmers are only able to obtain fair trade certification because they fought for land and organized themselves into strong cooperatives through state‐led agrarian reform programs. To explore the link between agrarian reform and fair trade, I review the history of agrarian reform in Nicaragua, describing how many of the country's fair trade‐certified cooperatives have roots in the reform programs of the 1980s. The review contributes to a broader historical perspective on the cooperative system at the heart of fair trade. It brings together scholarship with archived magazine articles to explore the connection between the contemporary fair trade system and the hard‐won successes of peasant movements for land reform.